Civil Legal Protection for Environmental Warriors - Andaniswari, Okky; Sulistianingsih, Dewi; Martitah, Martitah (Formosa Journal of Multidisciplinary Research, 2024)
The article analyzes civil law issues on the legal protection for environmental rights activists written in Permen LHK Number 10 (2024) upholds to protect the people who struggle to get the right for better environment. The main objective of the regulation is to protect for environmental activists from the criminal threat in accordance with Article 66 of Law Number 32 (2009) that guarantees anyone who focused to struggle in the environment cannot be criminalized. This type of research is normative law using examining statutory regulations approach by taking primary and secondary data. Qualitative analysis is also applied in this study. The results of the study show that the regulation aims to increase public participation between institutions to protect and to preserve the environment.